ARI updates 2018 - UiTM, Accounting Research Institute (Accounting Research Institute (ARI), 2018)
The Accounting Research Institute of Universiti Teknologi MARA, or ARI as it is popular known, has had an illustrious history despite its relative youth. With its humble beginnings in 2002 as part of a Special Interest Group initiative, the institute went on in 2009 to become just one of six centres of excellence in the country to be awarded the status of a Higher Institute Centre of Excellence (HICoE) by the Malaysian government. With its new position as a HICoE, ARI was tasked with becoming a global player in its niche area of Islamic Financial Criminology and in so doing, support a national shift to a new economic model based on innovation, creativity and high value added activities.